2008
DOI: 10.1021/nl080202+
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Electron and Hole Dynamics in Germanium Nanowires

Abstract: We present the first ultrafast time-resolved optical measurements, to the best of our knowledge, on ensembles of germanium nanowires. Vertically aligned germanium nanowires with mean diameters of 18 and 30 nm are grown on (111) silicon substrates through chemical vapor deposition. We optically inject electron-hole pairs into the nanowires and exploit the indirect band structure of germanium to separately probe electron and hole dynamics with femtosecond time resolution. We find that the lifetime of both electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
71
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 39 publications
13
71
1
Order By: Relevance
“…It is not surprising as the previous reports on ultrafast pump-probe studies of Ge nanowires also showed the decrease in s 1 with decreasing nanowire diameter due to the carrier trapping at the nanowire surface. 50,54 The s 2 scarcely depends on the size and the surface of the structure but is mainly due to electron-hole pair recombination. The s 2 value is larger for porous nanowalls obtained on 30 Hz grown sample.…”
mentioning
confidence: 99%
“…It is not surprising as the previous reports on ultrafast pump-probe studies of Ge nanowires also showed the decrease in s 1 with decreasing nanowire diameter due to the carrier trapping at the nanowire surface. 50,54 The s 2 scarcely depends on the size and the surface of the structure but is mainly due to electron-hole pair recombination. The s 2 value is larger for porous nanowalls obtained on 30 Hz grown sample.…”
mentioning
confidence: 99%
“…7−10 Although such sophisticated devices have been demonstrated, the investigation of the fundamental ultrafast carrier dynamics of semiconductor nanowire (NW) assemblies is so far limited to a small group of materials 11−13 and to qualitative analysis. 14,15 A quantitative translation of the photon response of NW assemblies to carrier dynamics in these structures is essential to exploit them in the design of nanoscale optoelectronic devices.…”
mentioning
confidence: 99%
“…This finding is generally consistent with several prior reports on surface recombination in semiconductor NWs. 13,14,16 Here we present the first quantitative analysis of a Ge NW−air metamaterial using the photon response of the assemblies to determine carrier dynamics. This analysis enables us to identify three time regimes for ultrafast recombination processes: Auger recombination (0−5 ps after photoexcitation), recombination via carrier trapping at fast surface states on the nanowires (5− 20 ps), and recombination via both fast and slow surface traps (20−200 ps).…”
mentioning
confidence: 99%
“…The electron relaxation dynamics upon band-gap excitation in germanium have been investigated by several femtosecond pump-probe studies in the visible [1][2][3]. However, none of those studies addressed the fastest time scales of the excitation process itself or the carrier-carrier scattering dynamics in the first few fs after excitation.…”
Section: Introductionmentioning
confidence: 99%